In vitro Antioxidant Activities of a Poly Herbal Preparation: Sarasvatha choorna - Karunaratne, Tika Dewayalage Nimal; Arawwawala, Liyanage Dona Ashanthi Menuka; Sugatharatana, Kahapola; Ariyawansa, Hettiarachchige Sammy; Silva, Hapangama Asitha De (Free Radicals and Antioxidants)
Objectives: Sarasvatha choorna is one of the polyherbal preparations used for the management of dementia and contains 12 medicinal plants and rock salt. It is well known that free radicals attack the brain tissue and cause dementia which lead to impair the memory performance. Therefore, an attempt was taken to investigate the antioxidant activities of the water extract and the ethanol extract of Sarasvatha choorna. Methods: Via ferric reducing antioxidant power (FRAP), oxygen radical absorbance capacity (ORAC), 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2-azino-bis (3 ethylbenzothiazoline-6-sulfonicacid) diammonium salt (ABTS) assays. Results: FRAP (295.67 ± 5.48mg Trolox equivalents/g of extract), ORAC (45.09 ± 0.79mg Trolox equivalents/g of extract) and ABTS (99.22 ± 4.96mg Trolox equivalents/g of extract) values of the ethanol extract was significantly higher than those of the water extract (FRAP: 170.01 ± 1.17 mg Trolox equivalents/g of extract; ORAC: 29.73 ± 2.60 mg Trolox equivalents/g of extract and ABTS: 47.17 ± 1.24 mg Trolox equivalents/g of extract). In contrast, DPPH scavenging ability of the water extract (9.89 ± 0.32mg Trolox equivalents/g of extract) was significantly higher than that of the ethanol extract (6.69 ± 0.0mg Trolox equivalents/g of extract). Conclusion: Sarasvatha choorna has potent antioxidant activities and may play a major role to attack free radicals which is one of causes for dementia.
Keywords: Antioxidants; Dementia; Sarasvatha choorna